2018
DOI: 10.21860/medflum2018_192885
|View full text |Cite
|
Sign up to set email alerts
|

Could smoking increase the risk for metabolic syndrome among patients with schizophrenia in a Croatian population?

Abstract: Sažetak. Cilj: Shizofreniju karakterizira visoka učestalost ovisnosti o pušenju, kao i visoka učestalost metaboličkog sindroma. Unatoč tome, malo se zna o učinku pušenja na komponente metaboličkog sindroma u toj bolesti. Cilj ovog rada bio je ispitati pridonosi li, i u kojoj mjeri, pojava ovisnosti o pušenju, koncentracijama lipida i glukoze u plazmi te vrijednostima indeksa tjelesne mase (BMI) u skupini hrvatskih pacijenata sa shizofrenijom. Ispitanici i metode: U istraživanju su sudjelovala 263 kronična paci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…These findings support prior report among antipsychotic-naïve first-episode psychosis patients from the Chinese population. However, they dif-fer from the results of studies among schizophrenic patients under antipsychotics treatment, revealing no significant contribution of smoking status to plasma lipid levels [48,49].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These findings support prior report among antipsychotic-naïve first-episode psychosis patients from the Chinese population. However, they dif-fer from the results of studies among schizophrenic patients under antipsychotics treatment, revealing no significant contribution of smoking status to plasma lipid levels [48,49].…”
Section: Discussioncontrasting
confidence: 74%
“…However, our results are in contrast with the findings of two studies investigating the potential relationship between smoking status and plasma lipid profiles among chronic medicated schizophrenia patients. Those two studies revealed no significant association between smoking and any lipid levels, including total cholesterol, LDL -c, HDL -c, and tri-glycerides [48,49]. Discrepancies in the results found between medicated and unmedicated patients suggest that antipsychotic medications might mask the effect of smoking on plasma lipids [48].…”
Section: Discussionmentioning
confidence: 96%